Longitudinal Bi‐directional Effects of Disordered Eating, Depression and Anxiety. (1st June 2017) - Puccio, Francis; Fuller‐Tyszkiewicz, Matthew; Youssef, George; Mitchell, Sarah; Byrne, Michelle; Allen, Nick; Krug, Isabel
Abstract: Objective: The present study aims to explore the potentially longitudinal bi‐directional effects of disordered eating (DE) symptoms with depression and anxiety. Method: Participants were 189 (49.5% male) adolescents from Melbourne, Australia. DE, depressive and anxiety symptoms were assessed at approximately 15, 16.5 and 18.5 years of age. Results: Analysis of longitudinal bi‐directional effects assessed via cross‐lagged models indicated that DE symptoms of eating and shape/weight concerns were risk factors for anxiety. Results also showed that depression was a risk factor for eating concerns. Conclusion: Our findings provide preliminary evidence that preventative measures designed to target concerns about eating and shape/weight might be most efficacious in reducing the transmission of effects between symptoms of DE, depression and anxiety. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.